PENGARUH PERCAKAPAN NEGATIF KELUARGA TERHADAP PEMEROLEHAN BAHASA ANAK USIA 3—4 TAHUN - Imron Maulana (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2021)
The effect of negative conversation occurs intensively in children aged 3-4 years because it is a period of imitation. This period is one of the stages of socialization that a child gets within his family's scope. This study aims to comprehensively examine the negative conversations that affect language acquisition, especially phonological acquisition, mainly acquiring vowels that occur in SM and NS. The research method used is a qualitative descriptive method. The study results revealed that negative conversation significantly affected children's language acquisition and its characteristics. The concrete reality at this stage, especially when the family says anything, then gradually the child brain area will process it. The child will repeat it. This phenomenon occurs repeatedly, and then it is not imagined that he will speak these words spontaneously. A child tends to say it without understanding the meaning. Still, it will affect his character if the negative sentences internalized to his thought. Adopting this negative conversation tends to have unideal characteristics because a child does not imitate his negative words. Still, he tries to understand the meaning uttered by the person closest to him. In this case, the study results reveal that negative conversations significantly affect children's language acquisition and affect their characteristics. The conclusion is that language acquisition through an unfavourable exchange is obtained by internal (family) factors and external factors.